An evaluation of economic benefits of Palo tide embankment in Barangay Candahug, Palo, Leyte a look into community resilience - Torres, Trisha Dominique B.; Daga, Maricris L.
This study evaluates the economic benefits of the Leyte Tide Embankment (LTE) project and its impact on community resilience in Barangay Candahug, Palo, Leyte. The LTE, constructed as a coastal defense measure against typhoons and storm surges, aims to protect approximately 33,000 residents and mitigate the adverse effects of natural disasters, particularly following the devastation caused by Typhoon Yolanda in 2013. Using a mixed-methods approach, this research assesses changes in household income, employment and business opportunities, tourism development, and infrastructure investments resulting from the project. It also examines how these economic impacts contribute to the community's capacity to adapt, absorb, and recover from coastal hazards. Findings indicate that the embankment has generated substantial economic benefits by creating jobs, stimulating local businesses, attracting visitors, and reducing disaster-related losses, thereby enhancing overall community resilience. The study provides valuable insights for policymakers and stakeholders to guide future infrastructure investments aimed at fostering sustainable economic growth and disaster risk reduction in coastal communities.